Kinetic studies on colonocyte metabolism of short chain fatty acids and glucose in ulcerative colitis. - Clausen, M R (1995)
Short chain fatty acids (SCFAs) are potentially valuable as a topical therapy for distal ulcerative colitis. The mechanism of action is unknown but may involve improved intracellular energy production as previous evidence indicates that colonocyte oxidation of butyrate is impaired in ulcerative colitis. No information is, however, available on human mucosal metabolism of acetate and propionate in either health or disease or the Vmax and Km values of butyrate oxidation. The aim of the study was to assess the kinetic parameters, Vmax and Km, of the complete oxidation of short chain fatty acids and glucose by human colonocytes and to explore whether a metabolic abnormality could be confirmed in patients with ulcerative colitis. Colonocytes were isolated from surgical specimens obtained from 14 patients with ulcerative colitis and eight control subjects. Incubations were performed in the presence of a concentration range of 14C-labelled acetate, propionate butyrate, and glucose. Oxidation rates were obtained by quantifying the production of 14CO2. Vmax and Km were calculated by computer fitting of the data to a Michaelis-Menten plot. No significant differences were shown in either Vmax or Km values of any of the SCFAs or glucose comparing controls and patients with ulcerative colitis. Comparing the results obtained regarding the individual SCFAs, the most striking difference was the considerably lower Km value of butyrate. The apparent Vmax of acetate tended to be higher than Vmax of propionate and butyrate. Vmax of glucose oxidation was significantly lower compared with the Vmax values of SCFA oxidation. The study shows the ability of isolated human colonocytes to utilise each of the three major SCFAs, but does not support a pathogenic role for defective metabolism of butyrate in ulcerative colitis. The considerably lower Km of butyrate oxidation supports a specific role of butyrate as an energy source for the colonic mucosa in both health and ulcerative colitis.